The Relationship Between Financial Ratios and Sales Performance in Listed Companies on the Indonesia Stock Exchange - Wardani, Megasuciati; Hwihanus, Hwihanus (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to analyze the relationship between working capital ratios, current ratios, debt to total assets ratios, and variables related to sales in companies listed on the Indonesia Stock Exchange. To determine the influence of working capital ratios, current ratios, and debt to total assets ratios on the sales performance of companies in the context of the Indonesian capital market. To identify factors that may affect or moderate the relationship between financial ratios and the sales performance of companies in the Indonesian capital market. This study utilizes secondary data from the Indonesia Stock Exchange (with Non-Probability sampling, specifically Convenience sampling. In this sampling technique, researchers select samples based on convenience and relevance to the variables under investigation. Data collection involves observation, structured interviews, and literature reviews. After obtaining the data, quantitative analysis will be conducted using the SPSS Version 26 application. Following the data processing, it can be concluded that the influence of financial ratios on sales indicates that all examined variables (Working Capital Ratio, Current Ratio, Debt to Total Assets Ratio, and Working Capital) significantly affect the sales of the company. This emphasizes the importance of effective financial management in enhancing sales performance. It suggests that companies need to carefully consider financial ratios and manage them effectively. For example, optimizing working capital, maintaining a balance between assets and current liabilities, and considering the appropriate capital structure for managing debt can contribute to increased sales.